Synergistic Fabrication of Dose-Response Chitosan/Dextran/β-Glycerophosphate Injectable Hydrogel as Cell Delivery Carrier for Cardiac Healing After Acute Myocardial Infarction - Chongjun Hua; Jing Liu; Xiuhong Hua; Xinyu Wang (SAGE Publishing, 2020)
The human mesenchymal stem cells (hMSCs) therapy offering an encouraging the new methods to establish the conveying on the chitosan (C)/dextran (D)/β-glycerophosphate (β-GP) loaded with hMSCs to enhance the acute myocardial infarctions. The synthesized hMSCs-CD@β-GP system displayed the ratio of determination modules, size of the pore, absorbency, and the swellings ratio in the assortment of the 65 ka, 149 ± 39.8 µm, 92.2%, 42 ± 1.38, and 29 ± 1.9, respectively. The fabricated hMSCs-CD@β-GP was highly stable and physicochemical investigated and confirmed the suitability of the materials for cardiac regeneration applications. The in vitro examinations of the injectable hydrogels with hMSCs-CD@β-GP have recognized that the improved survival rate of the cells, increased the pro-inflammatory expressions factors, pro-angiogenic factors analysis confirmed the promising results of the ejection of fractions, fibrosis area, vessel density with decreased infractions size, with suggesting that the remarkable improvement of the heart regenerative function after myocardial infarctions. The new synergistic approach of the injectable hydrogels with hMSCs could able appropriate for the effective treatment of cardiac therapies after acute myocardial infarctions.